Application of Think Pair Share Learning Model Assisted by Flipbook Media to Improve Learning Outcomes of Grade IV IPAS SDN 2 Datar - Sari, Nimas Wulan; Ardianti, Sekar Dwi; Santoso (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2025)
This research is motivated by the use of learning models and learning media which are still minimal in IPAS learning at SDN 2 Datar. This study aims to evaluate the impact of the Think Pair Share (TPS) learning paradigm, supported by flipbook media, on Improvving the learning outcomes of grade IV students at SDN 2 Datar. A quasi-experimental design with a single group pretest-posttest was the research methodology employed. This study uses primary data sourced from the results of students' pretest and posttest. The approach used in this study is a quantitative approach. The results showed that the average pretest score of 56.00 increased significantly to a posttest score of 89.63 or increased by 33.63 points. The results of the Paired Sample T-Test analysis showed a significance value of 0.000 (<0.05) which indicated a significant difference in learning outcomes before and after the intervention. The implications of this research for the world of education are to encourage the use of learning models assisted by learning media to improve learning outcomes. Through this research, teachers and schools can be convinced to use learning models and learning media as an effort to improve student learning outcomes.